2008
DOI: 10.1007/s00167-008-0571-5
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between anterior knee pain and femoral trochlear dysplasia? Assessment of lateral trochlear inclination by magnetic resonance imaging

Abstract: It may be very difficult to diagnose the pathology in patients with anterior knee pain. Patients with chronic anterior knee pain have been reviewed for the study. Our aim was to delineate the presence of subtle trochlear dysplasia by measuring lateral trochlear inclination (LTI) in axial magnetic resonance imaging (MRI) scans. While there were 109 knees in the study group with anterior knee pain (AKP), control group consisted of 74 knees without AKP. The LTI measurements were performed at the level of proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 24 publications
6
39
1
Order By: Relevance
“…In addition, we have noted that hypermobile patellae are often associated with trochlear dysplasia, a condition that came to the attention of the authors only after the early development stages of the procedure. In 2008, Keser et al suggested a relationship between AKP and trochlear dysplasia based on a low lateral trochlea inclination angle, 30 confirming the previous findings from Powers. 31 Some patients with AKP who were diagnosed as having hyperpressure syndrome and a tilted patella, do have trochlear dysplasia.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, we have noted that hypermobile patellae are often associated with trochlear dysplasia, a condition that came to the attention of the authors only after the early development stages of the procedure. In 2008, Keser et al suggested a relationship between AKP and trochlear dysplasia based on a low lateral trochlea inclination angle, 30 confirming the previous findings from Powers. 31 Some patients with AKP who were diagnosed as having hyperpressure syndrome and a tilted patella, do have trochlear dysplasia.…”
Section: Discussionsupporting
confidence: 71%
“…In male PFPS patients the superior cartilage thickness was significantly lower compared to male control subjects (MD males: −0.90 95% CI −1.78 to −0.02). Keser et al 38 reported a significantly higher incidence of trochlear dysplasia in knees of the patients with PFPS compared to the knees of the controls (OR 7.12; 95% CI 1.6 to 31.7) and significantly less lateral trochlear inclination in PFPS patients compared to controls (MD −4.20; 95% CI −6.04 to −2.36). None of the other evaluated variables were associated with PFPS 13 33 39 55 60 64 65…”
Section: Resultsmentioning
confidence: 99%
“…Dejour et al showed that trochlear dysplasia with a positive 'crossing sign' is present in 96 % of patients with PF disorders, while they recorded it only in 3 % of 194 controls [15]. More recently, Keser et al studied the occurrence of trochlear dysplasia using the lateral trochlea inclination index of Carrillion [18], in patients with AKP with no apparent aetiology, and found that it was present in 16.5 % of the 109 cases and in 2.7 % of the control group, which consisted of patients for meniscal pathology [21]. In this study, the authors recorded the same prevalence of trochlea dysplasia in controls with the study of Dejour, which was published 14 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…1) [17]. Trochlear dysplasia has been directly associated with both recurrent patellar dislocation [18][19][20] and AKP [21,22] in patients with patellar instability, since it has been observed in 96 % of patients with PF disorders and in only 3 % of controls [15,22]. The surgical correction of trochlear dysplasia is done with the sulcusdeepening trochleoplasty procedure, in which the elevated groove is eliminated and the abnormal sulcus is deepened [23][24][25]; this can also rarely be enriched by the addition of patellar osteotomy in order to achieve a better congruency between the two articulating bones [26].…”
Section: Introductionmentioning
confidence: 99%